Avaliação da qualidade do Programa de Saúde Auditiva Neonatal do município de São Paulo - Fichino, Silvia Nápole (2021)
Hearing integrity is critical to child development. It is recommended to implement a neonatal hearing health program for the identification, diagnosis and early intervention of hearing loss, taking advantage of neuronal plasticity and the critical period of development of children. In São Paulo, the largest city in Brazil, the hearing health program was implemented in 2010, in 18 municipal maternity hospitals, and it is necessary to evaluate the results of this action in hearing health, to verify aspects in its process that need revision. The objective of this research was to study the results of the program and to analyze the quality indicators of the neonatal hearing health program in the city of São Paulo. The maternity hearing screening database was analyzed, the results of diagnosis carried out in three reference centers, and intervention data obtained thriugh interviews with those responsible for children with confirmed hearing loss, in june 2018 to october 2019. Families who were absent in the process were interviewed to identify the reasons for lost to follow up. 75.969 babies were born alive during the study period, the screening coverage rate was 98,99%; 0,12% missed the retest; 0,39% were referred to the diagnosis. Of these, 37,2% were absent, and 3,33% were absent in the intervention. Up to one month of life, 98,69% performed the screening; 53,12% of those referred to the diagnosis completed it by the 3rd month and 56,66% of those referred for intervention started it up to 6 months. 30,46% of children with conductive disorders, 35,94% sensorineural and 2,35% of auditory neuropathy spectrum were diagnosed. 75,6% families of children diagnosed with hearing loss were interviewed, of which 46,1% had an indication for speech therapy, 70% used electronic devices. It was concluded that the city of São Paulo managed to implement the stage of neonatal hearing screening, in a hospital environment in a manner consistent with the guidelines, however, it still needs to improve strategies for the stages of diagnosis and intervention